Pulitzer's School : Columbia University's School of Journalism, 1903-2003 - Boylan, James R. (Columbia University Press, 2003)
Marking the centennial of the founding of Columbia University's school of journalism, this candid history of the school's evolution is set against the backdrop of the ongoing debate over whether journalism can?or should?be taught in America's universities. Originally known as ""the Pulitzer School"" in honor of its chief benefactor, the newspaper magnate Joseph Pulitzer, Columbia's school of journalism has long been a significant and highly visible presence in the journalism community. But at the turn of the twentieth century, when the school was originally conceived, journalism wa.